Response of stem cells from human exfoliated deciduous teeth (SHED) to three bioinductive materials – An in vitro experimental study - Prasanna T. Dahake; Nikita P. Panpaliya; Yogesh J. Kale; Mahesh V. Dadpe; Shrikant B. Kendre; Chetana Bogar (Saudi Dental Journal)
Introduction: Stem cells have unmatched capacity and potential for regeneration and when used alone or in combination with scaffolds to replace or repair damaged cells, can differentiate into any mature cell. Aim: To evaluate the functional differentiation potential of EMD (Enamel Matrix Derivative), MTA (Mineral Trioxide Aggregate) and Biodentine on Stem Cells from Human Exfoliated Deciduous teeth (SHED). Objective: To determine functional differentiation potential (osteogenic/odontogenic) of various biomaterials on SHED. Material and method: SHED derived from 5th linear passage after sub-culturing were treated with EMD, MTA and Biodentine individually and their effect on cell viability was compared and evaluated by MTT (3-4,5-dimethylthiazol-2-yl-2,5-diphenyltetrazolium bromide) assay for 7 days. Alizarin red S staining was used to assess mineralization potential of these materials by the staining calcium deposits for 14 days. The results were analyzed using One-way ANOVA, Post hoc Tukey’s test for multiple comparisons. Results: It was observed that EMD imparted the highest cell viability at the end of 7 days (p < 0.001) followed by Biodentine and MTA. Likewise EMD showed highest potential to enhanced mineralization and expression of dentine sialoprotein (p < 0.001) followed by Biodentine and MTA at the end of 14 days (p<0.001). Conclusion: It can be concluded that all the tested materials are bioinductive to SHED. EMD can be used for various vital pulp therapies as that of Biodentine and MTA with predictable as well as enhanced success rate. Keywords: Bioinductive materials, Cytotoxicity, Functional differentiation, SHEDs, Vital pulp therapy